L’éducation à l’environnement : l’idée de neutralité entre simplisme, positivisme et relativisme - Carole Voisin (Éducation et Socialisation)
This paper aims, through case studies, to question the approach of environmental education. It seeks to identify and understand difficulties on teachers’s approach, often caught between "moralism" and "relativism". Difficulties in the design and implementation of these teachings, however, recommended by the official instructions, in the context of school curriculum disciplines (Lange, 2011, Victor & Lange, 2012), do not explain everything. Precisely, temptation to avoid classroom debates and controversies seems to refer, in some cases, to a positivist view of science or to a questionable conception of what "elementary knowledge" should be. Otherwise, the framework of secularism (laïcity) can induce for the teacher an intention of strict neutrality, hardly compatible with citizenship education. In short, how to enable teachers to engage with a relative serenity in the implementation of environmental problems while guarding both illusion of neutrality and temptation to indoctrinate young pupils.